Conflitos socioambientais relacionados aos recursos hídricos na perspectiva do comitê da bacia hidrográfica do rio Japaratuba em Sergipe - Feitosa, Sheila Patricia Santos (2019)
The current development model has caused pressure on water resources and as a consequence triggered several socio-environmental conflicts. Lifting water uses in the basin and knowing conflicts is the first step in the search for negotiation within legitimate spaces such as river basin committees, as this forum has the function of debating, negotiating and arbitrating on water uses and their conflicts in the watershed with the different agents involved in water management. This research aimed to analyze the conflicts related to water resources from the committee's performance in the Japaratuba River Watershed from 2007 to 2017. And the specific objectives: to raise the types of water uses in the basin; typify the conflicts related to the water resources identified in the basin; identify and classify the parties involved in the conflict; build a map of environmental conflicts from the perspective of the Japaratuba River Watershed Committee (JRWMC). In general, this research analyzes the uses of water in the Japaratuba River basin in Sergipe and the acting of the Japaratuba River Watershed Committee (JRWMC) in relation to the treatment given the conflict complaints. The analysis was based on the minutes of meetings of this collegiate from 2007 to 2017. The conflicts were systematized according to the type, nature of the conflict, municipality of the basin, whistleblower segment and affected, and for better visualization of these conflicts in the municipalities of the basin, these were specialized in thematic map, using to this geoprocessing instruments. It was found that industrial supply is the use that required more water grants. Underground springs are the most used in 73% of the grants. Twelve (12) types of conflicts were identified. It was found that the Japaratuba River Watershed Committee (JRWMC) is well structured, was properly established, has internal rules, has water resource management instruments and in 2015 approved the basin plan, but limited political action is noted, in order to discuss and forward complaints of conflicts that result in significant effect, since conflicts are the same since his institution, some of them denounced year after year, but without viable solution to the actors involved.